2005
DOI: 10.1145/1163405.1163410
|View full text |Cite
|
Sign up to set email alerts
|

Automated assessment and experiences of teaching programming

Abstract: This article reports on the design, implementation, and usage of the CourseMarker (formerly known as CourseMaster) courseware Computer Based Assessment (CBA) system at the University of Nottingham. Students use CourseMarker to solve (programming) exercises and to submit their solutions. CourseMarker returns immediate results and feedback to the students. Educators author a variety of exercises that benefit the students while offering practical benefits. To date, both educators and students have been hampered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 12 publications
1
68
1
7
Order By: Relevance
“…However, learning to write computer programs is recognized to be a challenging subject for students due to the required logical thinking and the implied abstract concepts (Milne & Rowe, 2002;Robins et al, 2003;White & Sivitanides, 2002). Programming also poses a challenge to instructors because of the difficulty of grading student code in a fair and time-efficient manner (Cheang, 2003;Higgins, Gray, Symeonidis, & Tsintsifas, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, learning to write computer programs is recognized to be a challenging subject for students due to the required logical thinking and the implied abstract concepts (Milne & Rowe, 2002;Robins et al, 2003;White & Sivitanides, 2002). Programming also poses a challenge to instructors because of the difficulty of grading student code in a fair and time-efficient manner (Cheang, 2003;Higgins, Gray, Symeonidis, & Tsintsifas, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Higgins [37] stated that grading performed by CourseMarker tool in one section of a course was at par with the assessment done by a teaching assistant in some other section of same course. Also in 2012, Taherkhani [38] revealed that AARI (e-assessment tool) was successful at recognizing the algorithms used by the students to perform sorting on integers for about 75% of the submissions.Further in 2014, Gaudencio [39] stated that instructors who manually graded the assignments also tend to agree more with the feedback provided by the tool in comparison to assessment provided by other instructors.…”
Section: Rq4 Is the Results Ibtained By E-iassessment Tiils Precise Amentioning
confidence: 99%
“…He concluded that online assessment gave a more precise indication of student knowledge. In 2005, Higgins [28] conducted an experiment in which "CourseMarker substituted Ceilidh at the University of Nottingham", thus increasing the passing percentage of students. Also in 2005, "Malmi [30] showed results from students using TRAKLA and TRAKLA2", in which final exam grades improved when students were allowed to resubmit their work.…”
Section: Rq1 Have E-iassessment Tiils Laid a Pisitive Impact In Studmentioning
confidence: 99%
“…CourseMarker [12], Boss [13]. Correctness is checked through a comparison of the student's program solution and a model solution.…”
Section: Related Workmentioning
confidence: 99%